Probiotics and Herbals as a Boom in Treatment of Ulcerative Colitis - Bhattacharya, Sankha (Asian Journal of Pharmaceutics (AJP), 2020)
Ulcerative colitis (UC) is an inflammatory chronic disease primarily affecting the colonic mucosa; the extent and severity of colon involvement are variable. In its most limited form, it may be restricted to the distal rectum, while in its most extended form, the entire colon is involved. UC is identified by mucus diarrhea, tenesmus, bowel distension, and anemia. 5-aminosalicylic acid drugs, steroids, and immunosuppressant are used for therapy of UC. The annual occurrence of disease in Asia, America, and Europe was estimated to be 6.3, 19.2, and 24.3/100,000 people years. The main challenges in the management of the disease are drug-related side effects and local targeting. To overcome these challenges, probiotics overcome drug-related adverse side effects and local targeting. On ingestion, the probiotics can result in health beneficial effects. Probiotics are mainly used as gut modulators but are also nowadays explored for their use in UC.